Rumah Sakit Syariah Strategi Pemasaran Vs Syiar - Hayati, Mala; Sulistiadi, Wahyu (UI Scholars Hub, 2018)
The phenomenon of sharia awareness among the people of Indonesia, moves the economy in various aspects of people's lives, including the health service sector. The community begins to choose products that are not only quality from the medical side, but also get psychosocial safe services framed with Islamic values. Very open market opportunities to capture these symptoms. Sharia hospitals try to answer this challenge by packaging Islamic values into their service standards. Literature studies sourced from various scopus indexed international journals and google scholar. The concept of sharia hospitals that carry spiritual values is in line with the marketing 3.0 strategy that has the key concept of marketing vision, mission and values. This is the answer to the tendency of Muslim consumers who have chosen sharia products to fulfill their primary and secondary needs. Sharia Hospital was formed in an effort to integrate sharia values into all aspects of health services, administrative to patient service standards that are not owned by non-sharia hospitals. This is also a differentiation of hospital service products by targeting clear segmentation, although health services are essentially universal for all elements of society. Marketing standards must still be carried out which includes the internal-external and tangible-intangible aspects of a hospital, including the most important aspect is the quality of hospital services. So that Islam which is rahmatan lil alamin can become a syiar through a professional and trusted sharia hospital. Sharia hospitals that have a vision and carry values, still have to use marketing strategies to introduce their products, as well as Islamic teachings that protect human life.